The Announcement Effect and Choice between Rights Issues & Equity Carve-Outs : Empirical Evidence in Malaysia - Nie, Qing (2013)
There are 69 firms announced pure rights issue and 33 parent firms announced equity carve-out during the period of 2002 to 2011. From the abnormal return that generate from both samples, it shows rights issue announcement has a negative impact on the stock price and equity carve-out has a positive impact on the parent stock price. By using the t-test, there are empirical evidences suggested that the abnormal return might be exist for both equity offering approach. In addition, abnormal returns of them are significant in different days and the result also shows that the reaction of their recommendations on stock prices can be explained by different variables.Investors are suggested not to blindly follow the recommendations from investment advisers since advisers have different performances and their recommendations do not consistently provide abnormal return after the publication. The firms choose to raise their capital through different ways, however, if there are some certain variables that are significant in the firm as shown in this research, they might want to go for rights issue or equity carve-out for a better outcome. As a conclusion, this research provides a clear picture on how the results are found and how the recommendations from rights issue and equity carve-out announcement affect the stock price movements and the choices between those two approaches.